Executive Functioning: Assessing the Role of Perceived Paranormal Ability - Drinkwater, Kenneth Graham; Dagnall, Neil; Denovan, Andrew; Parker, Andrew; Escolà-Gascón, Álex (Frontiers in Psychology, 2021)
This study examined whether scores on self-report measures of executive functions varied in accordance with level of self-professed paranormal ability. The investigators compared three groups varying in attribution of paranormal facilities: practitioners (Mediums, Psychics, Spiritualists and Fortune-Tellers), self-professed ability and no ability. Consistent with recent research on cognitive-perceptual factors allied to delusional formation and thinking style, the researchers anticipated that practitioners would score higher on paranormal belief and self-reported executive function disruption. Correspondingly, the investigators also hypothesised that the self-professed ability group would demonstrate greater belief in the paranormal and higher levels of executive function disruption than the no ability group. A sample of 499 (219 males, 279 females) respondents completed the measures online. Multivariate analysis of variance (MANOVA) found a large effect size, alongside significant differences on all variables apart from Cognitive Reappraisal. Pairwise comparisons indicated that Paranormal Belief increased as a function of level of ability; practitioners scored higher than self-professed, who in turn scored higher than the no ability group. For executive functioning, significant differences emerged only for the no ability vs. self-professed ability and no ability vs. practising groups. Collectively, outcomes indicated that perception of ability, regardless of intensity of paranormal conviction, influenced subjective appraisal of executive functions. Failure to find consistent differences between practitioner and self-professed ability groups suggested that discernment of ability was sufficient to heighten awareness of executive functioning disruptions.